Comprehensive porosity determination of combustion-deposited SiOx thin films and correlation with FTIR signal - Kretzschmar, B. S. M.; Wendler, E.; Heft, Andreas; Koecher, R.; Voigt, C.; Ronning, Carsten; Gruenler, B.; Raedlein, E. (Surface & Coatings Technology, 2019)
Porous silicon oxide thin films were deposited by combustion chemical vapour deposition (CCVD). Depending on the process parameters applied, the layer thickness ranged from 18 to 165 nm, as obtained by profilometry and spectral ellipsometry (SE). The layer morphology was investigated by scanning electron microscopy (STEM) and atomic force microscopy (AFM) revealing roughnesses of the respective films between 0.1 and 42.4 nm. The porosity of the films was determined using weighing, SE, and Rutherford backscattering spectrometry (RBS) with all methods giving similar values. The porosity varied between 21 and 93%. These high porosities can be an effect of voids resulting from pores and roughness. The investigations revealed an open porosity. The received porosities were correlated with FTIR signal. The FTIR signal strength per unit volume Ψ correlates linearly with the porosity. This result can be used as a calibration curve. Thus, the porosity of an unknown silicon oxide layer can be deduced from the measured FTIR signal and the layer thickness. All methods applied here yield a consistent description of the layer properties.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Combustion chemical vapour deposition; Fourier transformed infrared spectroscopy; Porosity; Rutherford backscattering spectrometry; Silicon oxide; Spectral ellipsometry; Weighing